Large-Scale C++ LiveLessons-Workshop : Applied Hierarchical Reuse Using Bloomberg's Foundation Libraries - Lakos, John, 1959-; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2014)
"In this video training, John Lakos surveys problems associated with very large scale C++ development, and the cohesive techniques to address those problems, culminating in a proven component-based methodology refined through his practical experience at Bloomberg. The real-world application of this methodology-including three levels of aggregation, acyclic dependencies, nominal cohesion, fine-grained factoring, class categories, narrow contracts, and thorough component-level testing-will be demonstrated using the recently released open-source distribution of Bloomberg's foundation libraries. After watching the video, viewers will be in an excellent position to selectively delve deeper into the various separate aspects of this comprehensive development methodology. "--Resource description page.
Title from resource description page (viewed November 17, 2014).
Presenter, John Lakos.
Keywords: C++ (Computer program language); Electronic books